Retained non-previa placenta in the era of “placenta accreta spectrum”: a report of two cases managed expectantly and a proposed plan for management - Mohamad K. Ramadan; Mohamad K. Ramadan; Nouhad El-Zein; Murchida Jomaa; Abir Zeidan; Rana El Tal; Dominique A. Badr (Frontiers in Medicine)
Retained placenta (RP) is the absence of placental expulsion within 30 min of neonatal delivery. It is an obstetric complication affecting 0.5–4.8% of all vaginal deliveries. We report two cases in which the patients were primiparous. Patients were initially kept at the hospital under close observation. The lack of spontaneous detachment and the absence of bleeding prompted us to resort to an expectant approach approved by both patients. A decrease in B-hCG levels was followed by a steady decrease in placental size and the resumption of regular menses. The management of RP should be individualized according to hospital resources, patient fertility desire, sonographic characteristics, the presence of hemorrhage, and hemodynamic stability. RP should prompt the mobilization of resources needed for managing postpartum hemorrhage (PPH), which might ensue without notice. Manual removal of the placenta (MROP) has been recommended for managing RP regardless of hemorrhage or retention etiology. MROP, however, might initiate massive bleeding, infections, prolonged hospitalization, the need for curettage and hysterectomy. Moreover, if MROP is attempted in an unidentified placenta accreta spectrum (PAS), it might initiate life-threatening hemorrhage, necessitating the performance of hemostatic interventions, including emergent hysterectomy. Serious considerations should be given to mitigate the indiscriminate use of MROP in the era of the “PAS epidemic.”